Activated Carbon-Decorated Spherical Silicon Nanocrystal Composites Synchronously-Derived from Rice Husks for Anodic Source of Lithium-Ion Battery - Sankar Sekar; Abu Talha Aqueel Ahmed; Akbar I. Inamdar; Youngmin Lee; Hyunsik Im; Deuk Young Kim; Sejoon Lee (Nanomaterials, 2019)
The nanocomposites of activated-carbon-decorated silicon nanocrystals (AC<nc-Si>AC) were synchronously derived in a single step from biomass rice husks, through the simple route of the calcination method together with the magnesiothermic reduction process. The final product, AC<nc-Si>AC, exhibited an aggregated structure of activated-carbon-encapsulated nanocrystalline silicon spheres, and reveals a high specific surface area (498.5 m2/g). Owing to the mutualization of advantages from both silicon nanocrystals (i.e., low discharge potential and high specific capacity) and activated carbon (i.e., high porosity and good electrical conductivity), the AC<nc-Si>AC nanocomposites are able to play a substantial role as an anodic source material for the lithium-ion battery (LIB). Namely, a high coulombic efficiency (97.5%), a high discharge capacity (716 mAh/g), and a high reversible specific capacity (429 mAh/g after 100 cycles) were accomplished when using AC<nc-Si>AC as an LIB anode. The results advocate that the simultaneous synthesis of biomass-derived AC<nc-Si>AC is beneficial for green energy-storage device applications.